Psychological symptoms in high achieving students: The multiple mediating effects of parental achievement pressure, perfectionism, and academic expectation stress - Haspolat, Namık Kemal; Yalçın, İlhan (Psychology in the Schools, 2023)
The study aimed to investigate the correlations between psychological symptoms in high-achieving students with performance-oriented assessment, parental psychological control, parental achievement pressure, perfectionism, and academic expectation stress. The study group consisted of 1134 science high school students (658 females [57.1%], 486 males [42.9%]) aged between 14 and 19 years (mean = 16.26, SD = 0.871). In the research, the Classroom Assessment Environment Scale, Leuven Adolescent Perceived Parenting Scale, Parental Achievement Pressure Scale, Academic Expectation Stress Inventory, Child and Adolescent Perfectionism Scale, and Depression Anxiety Stress Scale-21 were used as data collection tools. The research, using the correlational survey model, analyzed the data with structural equation modeling. In the structural model, performance-oriented assessment and parental psychological control significantly predicted parental achievement pressure, while parental achievement pressure significantly predicted perfectionism, academic expectation stress, and psychological symptoms. Parental achievement pressure had a mediating role in the relationship between performance-oriented assessment and parental psychological control with psychological symptoms. Performance-oriented assessment and parental psychological control indirectly predicted psychological symptoms mediated by parental achievement pressure, perfectionism, and academic expectation stress. Based on the multigroup structural equation model, it was also seen that the structural model did not differ by gender.
Keywords: academic stress; anxiety; depression; high-achieving students; parental achievement pressure